2022
DOI: 10.3390/plants11081084
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Nitric Oxide and Abscisic Acid on the Cellular and Physiological Functioning of sub1A QTL Bearing Rice Genotype under Salt Stress

Abstract: Hydroponic culture containing 200 mM NaCl was used to induce oxidative stress in seedlings of cultivars initially primed with 1 mM SNP and 10 µM ABA. Exogenous application of sodium nitroprusside (SNP – a nitric oxide donor) and abscisic acid (ABA) was well sensitized more in cv. Swarna Sub1 than cv. Swarna and also reflected in different cellular responses. The major effects of salinity, irrespective of the cultivar, were lowering the water relation, including relative water content and osmotic potential, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…The response to aluminum (Al) toxicity in plants involves two primary pathways: exclusion and oxidative tolerance [40]. Exclusion involves several channel proteins on cell membranes and tonoplasts, aided by specific metabolites, including anion transporters like malate/hydroxide ion that facilitate Al sequestration into vacuoles or apoplastic spaces [41]. Solubility of various organic acid anions like citrate, lactate, oxalate, and succinate in acidic environments also plays a role [42].…”
Section: Metabolomes Induction To Aluminum Responses In Plantsmentioning
confidence: 99%
“…The response to aluminum (Al) toxicity in plants involves two primary pathways: exclusion and oxidative tolerance [40]. Exclusion involves several channel proteins on cell membranes and tonoplasts, aided by specific metabolites, including anion transporters like malate/hydroxide ion that facilitate Al sequestration into vacuoles or apoplastic spaces [41]. Solubility of various organic acid anions like citrate, lactate, oxalate, and succinate in acidic environments also plays a role [42].…”
Section: Metabolomes Induction To Aluminum Responses In Plantsmentioning
confidence: 99%
“…The response to Al toxicity in plants involves two primary pathways: exclusion and oxidative tolerance [40]. Exclusion mechanisms involve several channel proteins on cell membranes and tonoplasts, including anion transporters (like malate/hydroxide ion), that facilitate Al sequestration into vacuoles or apoplastic spaces [41]. The solubility of various organic acid anions like citrate, lactate, oxalate, and succinate in acidic environments also plays a role [42].…”
Section: Metabolome Induction To Aluminum Responses In Plantsmentioning
confidence: 99%
“…The results suggest that ABA increases Pro level dependent on NO production under NaCl stress (Table 1). The application of ABA and NO can improve the growth of rice by maintaining water homeostasis, sodium ion/potassium ion (Na + /K + ) ratio, elevating antioxidant enzyme activities and antioxidant contents under 200 mM NaCl stress (Saha et al, 2022; Table 1). Hsu and Lee, 2018 reveal that methionine sulfoxide reductase (MSR; catalyzed the reduction of methionine sulfoxide to methionine residues and alleviated ROS damage to proteins)-related gene expression is up-regulated in rice roots under salt stress, but when 0.3 mM Flu or 300 mM cPTIO is added, the effect is reversed (Hsu and Lee, 2018;Table 2).…”
Section: Saltmentioning
confidence: 99%
“…The results can be seen that NO acts cooperatively in ABA-induced antioxidant enzymes under salt tolerance. Using 200 mM NaCl-induced salt stress triggers the accumulation of H 2 O 2 and O 2 in rice, but when SNP and ABA are applied, these negative effects are reversed, following high levels of APX and glutathione S-transferase (GST, EC 2.5.1.18; Saha et al, 2022). Wu et al (2018) found that the concentrations of O 2 and MDA are increased in wheat seedlings under Mo condition, but these adverse effects can be relieved by exogenous ABA and SNP.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation